Patterns in the social representation of "hearing loss" across countries: how do demographic factors influence this representation?. (2nd December 2018) - Germundsson, Per; Manchaiah, Vinaya; Ratinaud, Pierre; Tympas, Aristotle; Danermark, Berth
Abstract: This study aims to understand patterns in the social representation of hearing loss reported by adults across different countries and explore the impact of different demographic factors on response patterns. The study used a cross-sectional survey design. Data were collected using a free association task and analysed using qualitative content analysis, cluster analysis and chi-square analysis. The study sample included 404 adults (18 years and over) in the general population from four countries (India, Iran, Portugal and UK). The cluster analysis included 380 responses out of 404 (94.06%) and resulted in five clusters. The clusters were named: (1) individual aspects; (2) aetiology; (3) the surrounding society; (4) limitations and (5) exposed. Various demographic factors (age, occupation type, education and country) showed an association with different clusters, although country of origin seemed to be associated with most clusters. The study results suggest that how hearing loss is represented in adults in general population varies and is mainly related to country of origin. These findings strengthen the argument about cross-cultural differences in perception of hearing loss, which calls for a need to make necessary accommodations while developing public health strategies about hearing loss.